2004
DOI: 10.1161/01.str.0000126891.93919.4e
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Proteasome System and Proteasome Inhibition: New Strategies in Stroke Therapy

Abstract: Background and Purpose-Proteasomes are large multicatalytic proteinase complexes that are found in the cytosol and in the nucleus of eukaryotic cells with a central role in cellular protein turnover. The ubiquitin-proteasome system (UPS) has a central role in the selective degradation of intracellular proteins. Among the key proteins whose levels are modulated by the proteasome are those involved in the control of inflammatory processes, cell cycle regulation, and gene expression. There are now overwhelming da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(69 citation statements)
references
References 136 publications
1
68
0
Order By: Relevance
“…It is known that nuclear factor-B (NF-B) translocates to the nucleus, where it binds to specific promoter sequences, initiating the transcription of NF-Bdependent genes, many of which are mediators of inflammatory response (25). In dopaminergic neurons of patients with PD, nuclear translocation of NF-B is enhanced (26), and proteasome inhibition suppresses the activities of NF-B by stabilizing the inhibitory protein IB (27). Moreover, we demonstrated that proteasome inhibition accelerated the appearance of ␣-synucleinpositive inclusion bodies and provided neuroprotection (28,29).…”
Section: Parkinson Disease (Pd)mentioning
confidence: 71%
“…It is known that nuclear factor-B (NF-B) translocates to the nucleus, where it binds to specific promoter sequences, initiating the transcription of NF-Bdependent genes, many of which are mediators of inflammatory response (25). In dopaminergic neurons of patients with PD, nuclear translocation of NF-B is enhanced (26), and proteasome inhibition suppresses the activities of NF-B by stabilizing the inhibitory protein IB (27). Moreover, we demonstrated that proteasome inhibition accelerated the appearance of ␣-synucleinpositive inclusion bodies and provided neuroprotection (28,29).…”
Section: Parkinson Disease (Pd)mentioning
confidence: 71%
“…Following activation by a wide array of mediators, including cytokines, bacterial toxins, or oxidative stress, the signal transduction cascade is initiated, which causes the phosphorylation of IkBα on Ser32 and -36 by IKK complex [19]. Phosphorylation of IkBα is followed by ubiquitination via the E3 ligase SCFβ TRCP and is targeted for proteasomal degradation by the 26S proteasome [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of UPS has been shown to regulate the PSD-95 degradation and ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor surface expression (12), suggesting a possible relationship between UPS and glutamatergic activities. Ubiquitination is a process involving three enzymes: E1 (ubiquitin-activating enzyme), E2 (ubiquitin-conjugating enzyme), and E3 (ubiquitin ligase) (13,14). Interactions between an E3 ligase and its target molecule are considered a key step in determining the selectivity of UPS for a target molecule and its subsequent proteasomal degradation, a process that is subject to intracellular modulation by various upstream regulators (14).…”
mentioning
confidence: 99%